Online Monitoring of Grid Connected Residential Photovoltaic System using Zigbee and Web Server - Syafii Ghazali; Roni Putra; Hasdi Putra (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The paper presents grid-tied PV monitoring system using wireless sensor networks.  The temperature and humidity parameters were measured using DHT22. While ACS 712 5A current sensor and Arduino voltage sensor modules were used to measure photovoltaic output current and voltage respectively. Web application has been developed in the base station using PHP programming web server to access the sensor nodes through Zigbee wireless data communication. The user can access the HTML web interface of Photovoltaic monitoring system through local Ethernet or Wi-Fi connection. The residential 1.25 kWp grid connected photovoltaic system used to test the developed monitoring system. The data received exactly same as data sensed from remote area with average delay time 3 to 4 seconds. The result shows the photovoltaic power generation caracteristics under clear sky, cloud cover, and rainy weather conditions. The power 608.12 Wp has been generated by the solar panel from 7.00 am to 6.00 pm or 6.7 kWh per day during clear sky. During intermittent cloud covered the photovoltaic power graph have shown fluctuation power profile and energy conversion were decreased as well as in raining weather condition. The electrical power has been generated by photovoltaic for almost 12 hours per day in tropics area, but energy conversion is highly influenced by weather conditions, especially cloud cover, overcast and rainy.